Black Phosphorus Quantum Dots as an Efficient Saturable Absorber for Bound Soliton Operation in an Erbium Doped Fiber Laser - Zhiteng Wang; Yanhua Xu; Sathish Chander Dhanabalan; Joice Sophia; Chujun Zhao; Changwen Xu; Yuanjiang Xiang; Jianqing Li; Han Zhang (IEEE Photonics Journal)
We have investigated the nonlinear and ultrafast photonics of chemically processed black phosphorus quantum dots (BPQDs) synthesized by the solvothermal treatment approach, with an average lateral size of about 2.48 $±$ 0.4 nm. BPQDs exhibit optical saturable absorption measured by the balanced twin-detector measurement system at the telecommunication band and have been demonstrated for the generation of passively mode-locking operation in an erbium-doped fiber laser. Either two-pulse or three-pulse bound state of soliton pulse has been obtained, making the best use of the BPQDs-based saturable absorber. Our work suggests that BPQDs might be developed as an efficient optical saturable absorber for ultrafast photonics applications.